ROBUST SPECTRAL MODEL FOR LOW METAL CONCENTRATION MEASUREMENT IN AQUEOUS SOLUTION REVEALS THE IMPORTANCE OF WATER ABSORBANCE BANDS - Putra, Alfian; Wijaya, Nanang Rahmat (Jurnal Sains dan Teknologi Reaksi, 2024)
ABSTRACT In this study, we focused on detection of metal ions at low concentration in aqueous solution by using NIRS. New “aquaphotomics” concept (Tsenkova, 2007) has become a powerful strategy to understand the spectral changes related to small concentration of solutes in aqueous solution. To improve the model accuracy it is important to understand why it is possible to detect the object of interest using NIRS. Although detectable, metals have no absorption in NIR region (Sakudo,et,al, 2007). However it is perhaps due to their vibrational modes that are modulated by forming complexes with organic molecules containing C-H, N-H and O-H bonds. Therefore, alteration of the vibrational mode of water matrix caused by metal can be detected by NIRS. In this study, we present NIR spectroscopy link to aquaphotomics as a tool to predict low concentration (0-10.mg L-1) of Mg(II), Zn(II), Mn(II) and Cd(II).Keywords : NIR spectroscopy, spectral changes, absorbance